PELAKSANAAN FUNGSI BADAN PERMUSYAWARATAN DESA DI DESA BUNTET KECAMATAN ASTANAJAPURA KABUPATEN CIREBON - Edi Suhaedi; Abdul Wahid; Rohadi Rohadi (Jurnal De Jure Muhammadiyah Cirebon, 2020)
BPD Desa Buntet in realizing better village governance is to make Village Regulations needed. Village regulations that are made must be based on existing problems and the community wants a Village Regulation to be made as an effort to solve problems. Initiatives can also come from the Village Head, the proposals are examined to cover all the needs of the villagers or the problem comes only from one particular group to fulfill their interests. The problem in this study is the implementation of the BPD function in Buntet Village, Astanajapura District, Cirebon Regency, and the factors that hinder the implementation of the BPD function in Buntet Village, Astanajapura District, Cirebon Regency. This research uses sociological juridical research. The data collection technique uses the literacy method. It also uses interview and documentation techniques. The method of data management and analysis used by researchers is qualitative. The results of the research and discussion show that the implementation of the supervisory function by the BPD in Buntet Village has been carried out well, this is driven by coordination and cooperation between institutions. Therefore, to carry out this supervisory function, the BPD management in Buntet Village can consider several aspects that surround and relate to this function, including coordination with their partners, the Buntet Village Government as the object of supervision. 2. That the obstacles in carrying out its functions. There are 2 (two) inhibiting factors, namely: First, the internal inhibiting factor is the lack of communication; do not understand the function of BPD comprehensively; lack of experience in community organizations; lack of ability in terms of scientific legal drafting concepts. Second, the external inhibiting factor is that the Buntet Village Community does not fully understand the functions carried out by the BPD and there is no socialization. Keywords: Implementation, Function, Village Consultative Body.